2015
DOI: 10.1016/j.ijsu.2015.06.079
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hypothermia in patients under general anesthesia: Is there a drawback of laminar airflow operating rooms? A prospective cohort study

Abstract: Intraoperative hypothermia is still common and should therefore receive serious attention. Advanced age, the use of a laminar airflow operating room and general surgeries are high risk factors of hypothermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 25 publications
1
26
2
5
Order By: Relevance
“…By directing the clean incoming airflows strategically, there is potential to lower the airflow rates, leading to energy savings that are beneficial for both the hospital's economy and the environment. Another possible advantage of using lower airflows in the OR is that this may reduce the cooling effect and thus decrease the risk for patient hypothermia, which has been shown to be a risk factor for SSI [15].…”
Section: Discussionmentioning
confidence: 99%
“…By directing the clean incoming airflows strategically, there is potential to lower the airflow rates, leading to energy savings that are beneficial for both the hospital's economy and the environment. Another possible advantage of using lower airflows in the OR is that this may reduce the cooling effect and thus decrease the risk for patient hypothermia, which has been shown to be a risk factor for SSI [15].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that the odds of becoming hypothermic were 1·53 (95% CI 1·19-1·96) for patients whose procedures were done in LAF rooms compared with patients whose procedures were done in traditional ORs. 54 Prior cost-effectiveness analyses found LAF to be more expensive than conventional ventilation systems. An Italian study 55 found that building costs increased 24% and annual operating costs increased 36%.…”
Section: Discussionmentioning
confidence: 99%
“…在大型楼宇建筑里, 在冷 却塔水中检测到军团菌 [46] . 研究还发现, 在医院环 境内, 在烧伤护理病房或ICU中不同过程产生的传染 性气溶胶会导致交叉感染 [47,48] ; 使用氧气面罩、牙科 的 电 动 设 备 以 及 手 术 过 程 也 会 有 空 气 污 染 的 风 险 [49,50] . 此外, 废水的飞溅以及家庭卫生间的冲水, 都有可能导致病原体的空气传播 [51,52] .…”
Section: 一定影响 室内微生物的浓度大概至少是室外的10unclassified